Titanium-containing multiphase electrode electrochemical dissolution rate quantitative analysis method

Through the 4D visualization method of high-temperature electrochemical in-situ CT device, the dissolution volume and area changes of the complex phase electrode are analyzed, and the geometric structure changes of the complex phase electrode are solved, efficient enrichment of titanium elements and optimization of electrolysis process are achieved, and electrolysis is improved Quality and utilization of products.

CN119198846APending Publication Date: 2024-12-27BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410375082.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art cannot effectively analyze the geometric structure changes of the complex phase electrodes during high-temperature electrochemistry, resulting in the impurities in the titanium oxide precursor affecting the quality of the electrolyte product, and lacks an efficient electrolysis method, making it difficult to directly utilize titanium slag.

Method used

The electrochemical dissolution rate of titanium-containing complex phase electrode was quantified and analyzed by using a high-temperature electrochemical in-situ CT device to quantify the dissolution volume and area changes of each phase of the complex phase electrode through a 4D visualization method, and obtain the dissolution rate of different positions over time. , current density and overpotential, realize the correlation between the evolution characterization of complex phase electrodes and the driving force-overpotential.

Benefits of technology

In-situ detection and quantitative analysis of the complex phase electrode are realized, the complete accuracy of the test results are ensured, the electrolytic process optimization is guided, and the enrichment efficiency of titanium elements and the quality of electrolyte products are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119198846A_ABST
    Figure CN119198846A_ABST
Patent Text Reader

Abstract

The invention discloses a quantitative analysis method for the electrochemical dissolution rate of a titanium-containing multiphase electrode, and belongs to the technical field of electrochemical metallurgy. The method is realized based on an in-situ CT device of high-temperature electrochemistry. The in-situ CT device comprises a quartz crucible, a stainless steel base, a furnace cover, a halogen lamp and stainless steel equipment, wherein the quartz crucible can be used for carrying out electrochemical electrolysis in-situ testing at high temperature; the stainless steel base is used for fixing the quartz crucible; the implementation method comprises the following steps: by utilizing the characteristic that the densities of all phases in the titanium-containing multiphase electrode are different, based on an in-situ CT device of high-temperature electrochemistry, respectively extracting dissolution volume and area parameter changes associated with time at different positions of all phases of the titanium-containing multiphase electrode by adopting a 4D visualization method, and analyzing the dissolution volume and area changes of all phases of the multiphase electrode to determine the concentration of the titanium-containing multiphase electrode. And respectively quantifying the dissolution rate, the current density and the overpotential of different positions of each phase along with time change. The method has the advantages of being high in safety and easy and convenient to implement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a quantitative analysis method for electrochemical dissolution rate of a titanium-containing composite phase electrode, and belongs to the technical field of electrochemical metallurgy. Background Art

[0002] Titanium metal has the advantages of low density, high specific strength, corrosion resistance, high temperature resistance, non-magnetic and non-toxic. Titanium has become an important strategic metal for national economic development and industrial upgrading. It is widely used in military, aerospace, shipbuilding, chemical and other fields. The titanium industry is the basis for supporting major national equipment materials. my country has rich reserves of titanium resources, but it is mainly low-grade vanadium-titanium magnetite, and its utilization rate is very limited. The raw materials for the preparation of titanium metal in my country still rely mainly on imports, which seriously restricts the healthy development of my country's titanium metal industry. In view of the basic national conditions of my country's large reserves of titanium ore and low grade, the development of low-grade titanium slag preparation technology for titanium metal is the key to solving the shortage of raw materials in my country's titanium industry.

[0003] Under the national dual-carbon strategy, ensuring the security of strategic mineral resources and the rational use of mineral resources is one of the important ways to achieve the dual-carbon goals. In view of the difficulty of "low-carbon" and efficient extraction of titanium from my country's complex vanadium-titanium magnetite, the latest research has proved that the combination of chemical / electrochemical reactions can be used to directly extract metallic titanium and titanium alloys from titanium-containing ores, and initial progress has been made in experimental research, but two key problems still need to be solved: the titanium oxide precursor used for electrolysis contains a large number of impurities, which affects the quality of the electrolysis product; the titanium oxide phase formed by the preparation of titanium ores in my country is complex, and there is a lack of corresponding short-process and efficient electrolysis methods. At present, the raw materials for the production of metallic titanium are mainly high-purity titanium dioxide or titanium chloride. There are many impurities in titanium slag, and it is difficult to effectively separate multi-phase impurities and enrich titanium in titanium slag; the high-temperature molten salt electrolysis process is difficult to perform in-situ visualization to obtain dynamic parameters due to its harsh external environment. It is in a black box reaction environment, the electrode geometry changes irregularly, and the potential is unstable, so it faces the challenge of difficult direct utilization of titanium slag. It is necessary to develop analysis methods for the electrochemical electrolysis process of titanium-containing composite electrodes, establish characterization of composite electrode evolution, and study the laws of dynamic interface evolution, so as to guide the optimization of the electrolysis process. Summary of the invention

[0004] In order to solve the problem that the existing methods cannot obtain the law of geometric structure change of complex phase electrodes in high-temperature electrochemical processes, the purpose of the present invention is to provide a method for quantitative analysis of electrochemical dissolution rate of titanium-containing complex phase electrodes, which can detect and quantitatively analyze the evolution law of geometric structure of each phase in titanium-containing complex phase electrodes over time in situ, that is, to realize the correlation between the evolution characterization of titanium-containing complex phase electrodes and driving force-overpotential, and quantify the dissolution rate, current density, and overpotential of each phase at different positions over time through the changes in dissolution volume and area parameters of each phase in titanium-containing complex phase electrodes at different positions associated with time. The device used in the present invention is simple to operate, and the high-temperature electrochemical process is consistent with the industrial molten salt electrolysis environment, which can ensure that the test results are complete and accurate.

[0005] To achieve the above object, the present invention adopts the following method:

[0006] The present invention discloses a method for quantitatively analyzing the electrochemical dissolution rate of a titanium-containing composite electrode. The method utilizes the characteristics of different densities of each phase in the titanium-containing composite electrode, uses an in-situ CT device based on high-temperature electrochemistry, and adopts a 4D visualization method to respectively extract the dissolution volume and area parameter changes associated with time at different positions of each phase of the titanium-containing composite electrode. By analyzing the dissolution volume and area changes of each phase of the composite electrode, the dissolution rate, current density, and overpotential at different positions of each phase that change with time are quantified. The in-situ CT device includes a quartz crucible that can perform in-situ testing of electrochemical electrolysis at high temperature, a stainless steel base for fixing the quartz crucible, a furnace cover for fixing the composite electrode, a halogen lamp for heating, and a stainless steel device that can penetrate X-rays for in-situ testing.

[0007] As an improvement of the method for quantitative analysis of the electrochemical dissolution rate of a titanium-containing composite electrode described in the present invention, the in-situ detection and quantitative analysis data of the method are input into an electrochemical workstation to analyze the evolution laws of different titanium-containing composite electrodes under different working conditions (current, voltage).

[0008] As an improvement of the quantitative analysis method of the electrochemical dissolution rate of a titanium-containing complex phase electrode described in the present invention, there are many types of titanium-containing complex phase electrodes to choose from, including but not limited to titanium metal electrodes containing other impurities (sponge titanium, titanium alloys, etc.), metal-doped titanium oxide electrodes, titanium carbon oxide electrodes, titanium carbon oxynitride electrodes, etc.

[0009] As an improvement of the method for quantitative analysis of the electrochemical dissolution rate of a titanium-containing composite electrode described in the present invention, the method obtains the in-situ electrochemical electrolysis parameters of the titanium-containing composite electrode based on an in-situ CT device of high-temperature electrochemistry, and quantitatively analyzes the electrochemical electrolysis dissolution process of the composite electrode. The high temperature refers to a temperature applicable range of up to 1100°C. That is, the temperature applicable range of the in-situ CT device is from room temperature to 1100°C.

[0010] As an improvement of the quantitative analysis method of the electrochemical dissolution rate of a titanium-containing composite electrode described in the present invention, the method adopts a 4D visualization method to distinguish the different densities of each phase in the composite electrode, and respectively extract the changes in the dissolution volume and area parameters of each phase in the electrode associated with time and position.

[0011] As an improvement of the method for quantitative analysis of the electrochemical dissolution rate of a titanium-containing composite electrode described in the present invention, the method quantifies the dissolution rate, current density, and overpotential of different positions of each phase in the composite electrode as they change over time by analyzing the changes in the dissolution volume and area of ​​different positions of each phase in the composite electrode as they change over time.

[0012] The method also includes: drawing a time-varying curve of the titanium-containing composite electrode according to the variation rules of the dissolution volume and area at different positions; and quantifying the time-varying dissolution rate, current density, and overpotential curve of different positions of each phase in the composite electrode by extracting the time-varying dissolution volume and area variation of each phase in the composite electrode.

[0013] The present invention discloses a method for quantitatively analyzing the electrochemical dissolution rate of a titanium-containing composite electrode, and the specific implementation steps are as follows:

[0014] Step 1: Reconstruct the three-dimensional morphological changes of multiple phases in the composite electrode based on the density difference, obtain the dissolution volume and surface area data of each phase at different positions of the titanium-containing composite electrode, and analyze the volume and surface area dissolved within 30 minutes of electrolysis.

[0015] Step 2: Dissolve the volume and surface area parameter changes according to the volume and surface area data at different positions obtained in step 1, and calculate the dissolution rate, current density, and overpotential associated with time at different positions of each phase of the titanium-containing composite electrode according to formula 1.

[0016] According to the electrolysis time t, Formula 1 is divided into N function segments, where N is greater than or equal to 5, and when N=5.

[0017] Formula 1: TiCON dissolution rate in the first stage: The first stage Fe dissolution rate:

[0018] The second stage TiCON dissolution rate: The second stage Fe dissolution rate:

[0019] The third stage TiCON dissolution rate: The third stage Fe dissolution rate:

[0020] The fourth stage TiCON dissolution rate: The fourth stage Fe dissolution rate:

[0021] TiCON dissolution rate in the fifth stage: The fifth stage Fe dissolution rate:

[0022] Formula 2: TiCON current density in the first section: The first section Fe current density:

[0023]

[0024] Second section TiCON current density: The second section Fe current density:

[0025]

[0026] The third section TiCON current density: The third section Fe current density:

[0027]

[0028] The fourth section TiCON current density: The fourth section Fe current density:

[0029]

[0030] The fifth section TiCON current density: The fifth section Fe current density:

[0031]

[0032] Formula 3: Dissolution process of Ti: (rate-controlling step),

[0033] Dissolution process of Fe: (rate-controlling step),

[0034] t is the electrolysis time, ρ1 is the density of TiCON, ρ2 is the density of Fe, V1 is the dissolution volume of the first electrode within 30 min, S1 is the dissolution surface area within 30 min; V2 is the dissolution volume of the first electrode within 30 min, S2 is the dissolution surface area within 30 min; V3 is the dissolution volume of the first electrode within 30 min, S3 is the dissolution surface area within 30 min; V4 is the dissolution volume of the first electrode within 30 min, S4 is the dissolution surface area within 30 min; V5 is the dissolution volume of the first electrode within 30 min, S5 is the dissolution surface area within 30 min.

[0035] Step 3: The overpotential η is calculated from the current density using the BV equation:

[0036] i=i0(e -αfη -e (2-α)fη ),

[0037] Where i0 is the exchange current density of the object electrode, which can be measured by the Tafel method; α represents the electrode reaction transfer coefficient, and in this process, α=0.5; is a constant, n is the number of charges transferred in the reaction, F is the Faraday constant, R is the gas constant, T is the temperature, and η is the overpotential.

[0038] Step 4: quantify the dissolution rate, current density, and overpotential at different positions of each phase as a function of time based on steps 2 and 3.

[0039] Beneficial effects:

[0040] 1. A quantitative analysis method of the electrochemical dissolution rate of a titanium-containing complex phase electrode of the present invention obtains in-situ electrochemical electrolysis parameters of the titanium-containing complex phase electrode in-situ based on an in-situ CT device of high-temperature electrochemistry, and quantitatively analyzes the electrochemical electrolysis dissolution process of the complex phase electrode. The present invention has the advantages of high safety and simple implementation.

[0041] 2. The present invention provides a quantitative analysis method for the electrochemical dissolution rate of a titanium-containing composite electrode. The method uses a 4D visualization method to utilize the density difference of each phase of the composite electrode to extract the changes in the dissolution volume and area parameters of each phase of the composite electrode associated with time.

[0042] 3. The present invention provides a quantitative analysis method for the electrochemical dissolution rate of a titanium-containing composite electrode, which analyzes the dissolution volume and area changes of each phase of the composite electrode, and quantifies the dissolution rate, current density, and overpotential of each phase at different positions over time. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Schematic diagram of an in-situ CT device used in a quantitative analysis method of the electrochemical dissolution rate of a titanium-containing composite electrode.

[0044] Figure 2 It includes furnace cover, electrode, capillary glass tube, quartz crucible and crucible base.

[0045] Figure 3 This is the structural diagram of the multiphase electrode.

[0046] Among them: 1-metal shell of in-situ CT device, 2-halogen lamp, 3-shell base, 4-furnace cover, 5-quartz crucible, 6-capillary glass tube, 7-electrode wire, 8-complex phase electrode, 9-crucible base. DETAILED DESCRIPTION

[0047] Next, we combine the titanium-containing composite electrode (TiC x O yN z The present invention is further described in detail with reference to the accompanying drawings of the specification, but the embodiments of the present invention are not limited thereto.

[0048] The schematic diagram of the in-situ CT device structure of a method for quantitative analysis of electrochemical dissolution rate of titanium-containing composite phase electrodes disclosed in this embodiment is as follows: Figure 1 As shown, the in-situ CT device includes an in-situ CT device metal shell 1, a halogen lamp 2, a shell base 3, a furnace cover 4, a quartz crucible 5, a capillary glass tube 6, an electrode wire 7, a multiphase electrode 8, and a crucible base 9, wherein the crucible base 9 is connected to the quartz crucible 5 by high-temperature glue, the crucible base 9 is connected to the shell base 3 by threads, and the electrode wire 7 and the multiphase electrode 8 are connected to the electrochemical workstation by leads.

[0049] The bottom of the quartz crucible is heated by a halogen lamp.

[0050] The molten salt is poured into the crucible from the top of the quartz crucible.

[0051] Among them, the furnace cover and the quartz crucible are sealed by a sealing ring combination.

[0052] Quartz crucible and crucible base Figure 2 As shown, the crucible base 9 with a cylindrical hole in the center can be used to place the quartz crucible 5. The titanium-containing composite electrode structure is as follows Figure 3 As shown, Fe element is irregularly distributed in TiC x O y N z in the matrix.

[0053] This embodiment discloses a method for quantitatively analyzing the electrochemical dissolution rate of a titanium-containing composite electrode, and the specific implementation steps are as follows:

[0054] Step 1: Anode is TiC x O y N z With Fe composite electrode, the cathode is nickel wire, and the composite electrode: TiC in the electrochemical electrolysis process x O y N zThe geometric structure changes of the two phases Fe and Fe are extracted to extract the evolution of dissolved volume and area over time. The crucible base 9 connected to the quartz crucible 5 by high temperature glue is connected to the shell base 3 through a thread, the electrode wire 7 and the multiphase electrode 8 are fixed on the furnace cover 4 and placed in the quartz crucible 5, the electrode wire 7 and the multiphase electrode 8 are connected to the electrochemical workstation through a lead, and the molten salt is poured into the quartz crucible 5, and the electrode wire 7 and the multiphase electrode 8 are fixed on the furnace cover 4 and placed in the quartz crucible 5. The bottom of the quartz crucible 5 is heated to the working temperature by a halogen lamp, and the protective shell adopts a double-layer structure, and the temperature is kept stable by water circulation; the quartz crucible is fixed on a rotating base, and the electrode is connected to the electrochemical workstation through a sealing cover to realize in-situ observation of the electrolysis process. After the X-ray penetrates the quartz crucible, the data of the electrode geometry in the high-temperature in-situ electrochemical process is collected through the X-ray fluorescent screen.

[0055] Step 2: Use AVIZO to reconstruct the three-dimensional morphology changes of multiple phases in the composite electrode based on the density difference, obtain the volume and surface area data of each phase at different positions of the titanium-containing composite electrode, and analyze the volume and surface area dissolved within 30 minutes of electrolysis.

[0056] Step 3: According to the volume and surface area data at different positions obtained in step 2, the volume and area parameters of the dissolution are changed. According to the formula, the dissolution rate, current density, and overpotential associated with time at different positions of each phase of the titanium-containing composite electrode can be obtained. t is the electrolysis time of 30 minutes, ρ1 is the density of TiCON, and ρ2 is the density of Fe. V1 is the dissolution volume of the first section of the electrode within 30 minutes, and S1 is the dissolution surface area within 30 minutes; V2 is the dissolution volume of the first section of the electrode within 30 minutes, and S2 is the dissolution surface area within 30 minutes; V3 is the dissolution volume of the first section of the electrode within 30 minutes, and S3 is the dissolution surface area within 30 minutes; V4 is the dissolution volume of the first section of the electrode within 30 minutes, and S4 is the dissolution surface area within 30 minutes; V5 is the dissolution volume of the first section of the electrode within 30 minutes, and S5 is the dissolution surface area within 30 minutes.

[0057] Formula 1: TiCON dissolution rate in the first stage: The first stage Fe dissolution rate:

[0058] The second stage TiCON dissolution rate: The second stage Fe dissolution rate:

[0059] The third stage TiCON dissolution rate: The third stage Fe dissolution rate:

[0060] The fourth stage TiCON dissolution rate: The fourth stage Fe dissolution rate:

[0061] TiCON dissolution rate in the fifth stage: The fifth stage Fe dissolution rate:

[0062] Formula 2: TiCON current density in the first section: The first section Fe current density:

[0063]

[0064] Second section TiCON current density: The second section Fe current density:

[0065]

[0066] The third section TiCON current density: The third section Fe current density:

[0067]

[0068] The fourth section TiCON current density: The fourth section Fe current density:

[0069]

[0070] The fifth section TiCON current density: The fifth section Fe current density:

[0071]

[0072] Formula 3: Dissolution process of Ti: (rate-controlling step),

[0073] Dissolution process of Fe: (rate-controlling step),

[0074] The overpotential n can be calculated from the current density using the BV equation: i = i0 (e -αfη -e (2-α)fη ), where i0 is the exchange current density of the object electrode, which can be measured by the Tafel method; α represents the electrode reaction transfer coefficient, and in this process, α=0.5; is a constant, n is the number of charges transferred in the reaction, F is the Faraday constant, R is the gas constant, T is the temperature, and η is the overpotential.

[0075] Step 4: quantify the dissolution rate, current density, and overpotential at different positions of each phase as a function of time based on step 3.

[0076] This embodiment is used to study the dissolution volume and area changes of each phase over time, dissolution rate, current density, and overpotential quantitative analysis of the electrochemical electrolysis process of different types of titanium-containing composite electrodes under different working conditions (current, voltage). The 4D visualization method (in-situ CT device based on high-temperature electrochemistry) uses the density characteristics of different phases of the composite electrode to achieve real-time observation of the geometric structure changes of the titanium-containing composite electrode over time / space, analyze the dissolution volume and area changes of each phase of the composite electrode over time / space, and quantify the dissolution rate, current density, and overpotential of each phase over time at different spatial positions.

[0077] According to the above description, the embodiments are only used to illustrate the technical solutions of the present invention rather than to limit them. The present invention is described in detail with reference to the above embodiments. Those skilled in the art can still modify or replace the specific implementations of the present invention with equivalents. Any modifications or equivalents that do not deviate from the spirit and scope of the present invention are within the scope of protection of the pending claims. In addition, although some specific terms are used in this specification, these terms are only for convenience of description and do not constitute any limitation to the present invention.

Claims

1. A quantitative analysis method for the electrochemical dissolution rate of a titanium-containing composite electrode, characterized in that: Taking advantage of the different densities of each phase in the titanium-containing complex phase electrode, an in-situ CT device based on high-temperature electrochemistry and a 4D visualization method are used to extract the changes in the dissolution volume and area parameters associated with different positions of each phase of the titanium-containing complex phase electrode and time. By analyzing the changes in the dissolution volume and area of ​​each phase of the complex phase electrode, the dissolution rate, current density and overpotential of each phase at different positions that change with time are quantified. The in-situ CT device includes a quartz crucible that can perform in-situ testing of electrochemical electrolysis at high temperature, a stainless steel base for fixing the quartz crucible, a furnace cover for fixing the complex phase electrode, a halogen lamp for heating, and stainless steel equipment that can penetrate X-rays for in-situ testing.

2. A method for quantitative analysis of electrochemical dissolution rate of titanium-containing composite electrodes according to claim 1, characterized in that: The titanium-containing composite phase electrode includes but is not limited to titanium metal electrodes containing other impurities, metal-doped titanium oxide electrodes, titanium carbon oxide electrodes, and titanium carbon oxynitride electrodes; the titanium metal electrodes include sponge titanium and titanium alloys.

3. A method for quantitative analysis of electrochemical dissolution rate of titanium-containing composite electrodes according to claim 1, characterized in that: The in-situ CT device based on high-temperature electrochemistry obtains the in-situ electrochemical electrolysis parameters of the titanium-containing composite electrode and quantitatively analyzes the electrochemical electrolysis dissolution process of the composite electrode.

4. A method for quantitative analysis of electrochemical dissolution rate of titanium-containing composite electrodes according to claim 1, characterized in that: A 4D visualization method is adopted to distinguish the different densities of each phase in the multiphase electrode, and the changes in the dissolution volume and area parameters of each phase in the electrode associated with time and position are extracted respectively.

5. A method for quantitative analysis of electrochemical dissolution rate of titanium-containing composite electrodes according to claim 1, characterized in that: By analyzing the changes in the dissolution volume and area of ​​each phase at different positions in the multiphase electrode over time, the dissolution rate, current density, and overpotential at different positions of each phase in the multiphase electrode over time are quantified.

6. A method for quantitative analysis of electrochemical dissolution rate of titanium-containing composite electrodes according to claim 1, characterized in that: The time-varying curve of the dissolution volume and area at different positions of the titanium-containing composite electrode is drawn according to the variation law of the dissolution volume and area at different positions. The dissolution rate, current density and overpotential curve of each phase at different positions of the composite electrode are quantified by extracting the time-varying dissolution volume and area changes of each phase in the composite electrode.

7. A method for quantitative analysis of electrochemical dissolution rate of a titanium-containing composite electrode according to claim 1, 2, 3, 4, 5 or 6, characterized in that: The implementation steps are as follows: Step 1: reconstruct the three-dimensional morphological changes of multiple phases in the composite electrode based on the density difference, obtain the dissolved volume and surface area data of each phase at different positions of the titanium-containing composite electrode, and analyze the volume and surface area dissolved within 30 minutes of electrolysis; Step 2: Dissolve the volume and surface area parameter changes according to the volume and surface area data at different positions obtained in step 1, and calculate the dissolution rate, current density, and overpotential associated with different positions and time of each phase of the titanium-containing composite electrode according to formula 1; Divide formula 1 into N segments according to the electrolysis time t, and when N is greater than or equal to 5, when N = 5; Formula 1: TiCON dissolution rate in the first stage: The first stage Fe dissolution rate: The second stage TiCON dissolution rate: The second stage Fe dissolution rate: The third stage TiCON dissolution rate: The third stage Fe dissolution rate: The fourth stage TiCON dissolution rate: The fourth stage Fe dissolution rate: TiCON dissolution rate in the fifth stage: The fifth stage Fe dissolution rate: Formula 2: TiCON current density in the first section: The first section Fe current density: Second section TiCON current density: The second section Fe current density: The third section TiCON current density: The third section Fe current density: The fourth section TiCON current density: The fourth section Fe current density: The fifth section TiCON current density: The fifth section Fe current density: Formula 3: Dissolution process of Ti: Dissolution process of Fe: t is the electrolysis time, ρ1 is the density of TiCON, ρ2 is the density of Fe, V1 is the dissolution volume of the first electrode within 30 min, S1 is the dissolution surface area within 30 min; V2 is the dissolution volume of the first electrode within 30 min, S2 is the dissolution surface area within 30 min; V3 is the dissolution volume of the first electrode within 30 min, S3 is the dissolution surface area within 30 min; V4 is the dissolution volume of the first electrode within 30 min, S4 is the dissolution surface area within 30 min; V5 is the dissolution volume of the first electrode within 30 min, S5 is the dissolution surface area within 30 min; Step 3: The overpotential η is calculated from the current density using the BV equation: i=i0(ie -αfη -have been (2-α)fη ), Where i0 is the exchange current density of the object electrode, which can be measured by the Tafel method; α represents the electrode reaction transfer coefficient, is a constant, n is the number of charges transferred by the reaction, F is the Faraday constant, R is the gas constant, T is the temperature, and η is the overpotential; Step 4: quantify the dissolution rate, current density, and overpotential at different positions of each phase as a function of time based on steps 2 and 3.

8. A method for quantitative analysis of electrochemical dissolution rate of titanium-containing composite electrodes according to claim 7, characterized in that: Take α=0.5.